A 3-center comparison of 1-year mortality outcomes between transcatheter aortic valve implantation and surgical aortic valve replacement on the basis of propensity score matching among intermediate-risk surgical patients - Piazza, Nicolo; Kalesan, Bindu; van Mieghem, Nicolas; Head, Stuart; Wenaweser, Peter; Carrel, Thierry P; Bleiziffer, Sabine; de Jaegere, Peter P; Gahl, Brigitta; Anderson, Robert H; Kappetein, Arie-Pieter; Lange, Ruediger; et al. (JACC. Cardiovascular interventions, 2013)
This study sought to compare all-cause mortality in patients at intermediate surgical risk undergoing transcatheter aortic valve implantation (TAVI) or surgical aortic valve replacement (SAVR). Physicians are selecting "lower" surgical risk patients to undergo TAVI. No clinical data exist about the clinical outcomes of TAVI versus SAVR among intermediate-surgical-risk patients. We prospectively enrolled symptomatic patients with severe aortic stenosis who underwent TAVI or SAVR. Propensity-score matched pairs of TAVI and SAVR patients with Society of Thoracic Surgeons (STS) scores between 3% and 8% made up the study population. Primary endpoint was all-cause mortality at 1 year. Between November 2006 and January 2010, 3,666 consecutive patients underwent either TAVI (n = 782) or SAVR (n = 2,884). Four hundred five TAVI patients were matched to 405 SAVR patients. Of matched TAVI patients, 99 (24%) patients had STS scores <3%, 255 (63%) had scores between 3% and 8%, and 51 (13%) had scores >8%. Among patients with STS scores between 3% and 8%, 20 (7.8%) versus 18 (7.1%) patients had died up to 30 days (hazard ratio: 1.12, 95% confidence interval: 0.58 to 2.15, p = 0.74) and 42 (16.5%) versus 43 (16.9%) patients had died up to 1 year (hazard ratio: 0.90, 95% confidence interval: 0.57 to 1.42, p = 0.64) after TAVI and SAVR, respectively. Effects of treatment on 1-year mortality were similar across all subgroups except for sex, with some evidence for a beneficial effect of TAVI in women but not in men (test for interaction p = 0.024). Cumulative all-cause mortality at 30 days and 1 year was similar among propensity-score matched TAVI and SAVR patients at intermediate surgical risk. (Surgical Replacement and Transcatheter Aortic Valve Implantation [SURTAVI]; NCT01586910).